Investigating methods of capturing and sharing learning experience during field trip to support students activity - Allwihan, Ragad Mohammad (2015)
Field trips provide memorable experiences that help students to understand different aspects of natural sciences. They are considered as essential and effective teaching methods to use in environmental sciences such as geography, biology, and architecture (Rieger and Gay, 1997). Traditional methods for capturing experiences during field trips include documentation in the form of student note-taking and photographs. Whilst these are easy to use in the field, effort is required to convert this information into a format that can be easily shared with others and used to write up reports after the field trip event. Recent developments in digital and mobile technologies provide students with a range of software applications that could be used to facilitate capture and sharing of the field trip experience. These technologies offer additional advantages such as social interactivity, connectivity, individuality, portability and context sensitivity (Klopfer et al., 2002). The focus of this PhD research was to understand the role of smart mobile technology in supporting note taking activities during field trips. In addition, this research aimed to investigate the impact of using these devices to enhance field experiences in different contexts. A series of case studies were conducted with undergraduate students from different disciplines who conduct field studies as part of their coursework (geography and architecture). Consideration was also given to the clinical practice context for nursing students. Previous studies had examined the use of mobile devices in educational field trips but none had assessed the use of generic mobile technologies such as the new generation of smart mobile devices. In recognition of the increasing availability and use of these smart mobile devices, this research identified user requirements for information capture and sharing in field studies as well as the development of generic guidelines for design and implementation of mobile applications and tools in forthcoming years. The research provided an understanding of generic requirements (and context-specific requirements) in order to inform recommendations for use of mobile technologies in field study activities. This required understanding specific goals of the users to perform specified task in specific environments in the context of usability, effectiveness, efficiency and satisfaction toward (Bevan, 1995). In the initial stages of the research, three contexts of use for development of knowledge and practical skills in undergraduate students were considered. Four main studies were conducted, utilising a qualitative approach and applying a variety of methods. The characteristics of the target users, the understanding and meaning of their field experience, the kind of support that the mobile technology could usefully provide in the fieldwork were identified. The later stages of the research focused on the field trip excursions made by geography students and architecture students and considered the applicability of the research outcomes to the nursing students context in order to examine generalisability of the recommendations. The overall outcomes of this research show that current generation of mobile devices such as smart phones and tablets play a positive role in enhancing the capturing and sharing learning experience in undergraduate field trips. However, the enhancement is appeared when the participants are provided with training to familiarise them with use of the mobile devices before going into the field. The contribution of this thesis is the identification of user needs and requirements, and an understanding of what makes mobile technology good to use in the field. Recommendations are provided that could influence the education sector to consider the smart mobile devices as field equipment and to find ways to encourage students to use them in the field.